Mortality and Years of Life Lost due to Burn Injury Among Older Iranian People; a Cross-Sectional study - Sadeghian, Farideh; Saeedi Moghaddam, Sahar; Ghodsi, Zahra; Mehdipour, Parinaz; Ghanbari, Ali; O’Reilly, Gerard; Rezaei, Nazila; Mohammadi Fateh, Sahar; H. Mokdad, Ali; Rahimi-Movaghar, Vafa (Archives of Academic Emergency Medicine, 2022)
Introduction: The mortality of burn injury is a serious health problem among older people. The present study aimed to determine the epidemiological characteristics of burn mortality and Years of Life Lost (YLLs) among people aged ≥ 60. Methods: The National and Subnational Burden of Disease (NASBOD) study includes population-based cross-sectional data from the death registration system of Iran and those recorded by the cemeteries of Tehran and Esfahan were used in this study. Spatio-temporal and Gaussian process regression models were applied to estimate rates and trends of mortality and cause-specific mortality fractions. YLLs were calculated using Iranian life expectancy and the number of deaths. Results: The mortality rate for 1990 and 2015 was 17.4 and 4.5 per 100,000, respectively. From 1990 through 2015, the annual percentage of change in burn mortality rate was -6.1% in females and -4.4% in males. During 2015, there were 326 deaths following burns in people aged 60+ with 4586 person YLLs, and in 1990 there were 523 deaths with 4862 person-YLLs. The male-female ratio for 1990 and 2015 were 0.80 and 0.88, respectively. The age-standardized mortality rate was higher than 8.5 per 100,000 in border provinces in 2015. The provinces with better socioeconomic situations, such as Tehran, had a lower mortality rate than poor provinces, such as Sistan va Baluchistan. Conclusion: Although burn mortality in old people decreased in those 26 years, it is still high compared to high-income countries. Continued efforts to increase preventive measures and adequate access to quality care, especially in border provinces, is suggested.